Optical spectrum of HDE 245770 /A0535 + 26/ - R. A. Wade; J. B. Oke (The Astrophysical Journal, 1977)
Accurate O-serotyping of Escherichia coli remains essential for clinical surveillance, outbreak investigation, and evaluation of vaccines targeting invasive E. coli disease. Traditional agglutination-based serotyping is labor-intensive, low-throughput, and reliant on subjective visual interpretation. We developed a high-throughput (HTP) 96-well agglutination assay incorporating automated OD normalization (BioTek Epoch) and objective agglutination quantification using a CTL ImmunoSpot reader. A data-driven positivity cutoff (Total Intensity of Spots per Well < 11.65) was established via Youden's index to optimize diagnostic discrimination. Validation was performed in a GCLP-compliant laboratory using clinical isolates representing the nine O-serogroups included in the ExPEC9V vaccine candidate. The assay demonstrated 100% sensitivity across all homologous O-serogroups (n = 9) and ≥95% specificity across heterologous O-serogroups, including five non-ExPEC9V clinical isolates. Robustness was confirmed for bacterial suspensions with OD 600 values of 0.6-1.2, the range recommended for clinical implementation. Long-term stability of boiled cultures stored at 2-8°C was inconsistent-particularly for O75 antisera-supporting same-day preparation of suspensions. Due to heat-associated interference observed with deep-well plastic blocks, glass 96-well tube systems were validated and adopted for clinical testing, demonstrating 100% specificity across all heterologous O-serogroups. This validated HTP agglutination assay provides a scalable, reproducible, and clinically actionable method for E. coli O-serotyping. By preserving the immunologic specificity of conventional agglutination while enabling automation and objective readouts, the assay is well suited for vaccine efficacy studies, reference laboratory workflows, and clinical microbiology programs requiring accurate phenotypic confirmation of O-antigen expression.IMPORTANCEAgglutination serotyping of bacterial isolates is labor-intensive, requires specialized laboratories and skilled personnel, and relies on subjective visual interpretation. Nevertheless, it remains essential for determining O-antigen expression, providing information that molecular methods-focused only on detecting serotype-specific genes-cannot. For this reason, agglutination O-serotyping continues to serve as the regulatory accepted gold standard. This study describes the development, optimization, and validation of a high-throughput agglutination O-serotyping assay designed to overcome the constraints of low throughput and operator-dependent variability. The validated assay demonstrated its scientific utility through the characterization of clinical isolates from a Phase 3 trial of a candidate Escherichia coli vaccine.CLINICAL TRIALSThis study is registered with ClinicalTrials.gov as NCT04899336.